Money and materiality in the golden age of graphic satire - Lahikainen, Amanda (Studies in seventeenth- and eighteenth-century art and culture, 2022)
Value & the inflation of Georgian graphic satire -- Crisis -- Subjectivity & trust -- Imitation & immateriality -- Materiality -- Epilogue: Deflation -- Appendix: Beyond Britain.